Adsorption of bovine serum albumin and nanocrystallines on biomedical alloys. Issue 1 (19th December 2016) - Wang, Linghe; Qiao, Lijie; Yan, Yu
Abstract : Orthopaedic prostheses are lubricated by pseudosynovial fluids that contain various proteins. The process of the adsorption can affect the lubrication and corrosion behaviours of such devices and eventually influence their safety. This paper addresses the role of the most abundant protein in the synovial fluid, albumin, on tribocorrosion properties of a cobalt (Co)-based biomedical alloy. A fluorescence imaging technique was used to observe the adsorption of albumin. The open circuit potential of cobalt–chromium (Cr)–molybdenum (Mo) alloy could drop by 330 mV under tribological contact (8 h), which would result in an acceleration of the corrosion rate. Atomic force microscopy (AFM) and scanning Kelvin probe force microscopy (SKPFM) measurements were performed to characterise the surface topography and the surface potential. Small-angle X-ray scattering (Saxs) was applied to measure the size and distribution of the nanocrystallines at the rubbing surfaces. As a general conclusion, wear could promote the adsorption of albumin and the amount of adsorbed protein increased as the time of sliding progressed. However, it had little effect on the size of the nanocrystals at the surface. The size of the nanocrystals induced by the mechanical tribology motion was around 6 nm with or without electrochemical corrosion reactions.